Evidence for a causal relationship between the structure, size, and load of calcium pyrophosphate dihydrate crystals, and attacks of pseudogout. - Swan, A (1995)
OBJECTIVE--To investigate any relationship between the nature, size, and numbers of synovial fluid (SF) calcium pyrophosphate dihydrate (CPPD) crystals, and attacks of pseudogout. METHODS--Knee SF was aspirated from nine selected patients, first during an attack of pseudogout (acute sample) and again later when the attack had subsided (interval sample). CPPD crystals were extracted, weighed, examined by high resolution transmission electron microscopy (HRTEM), and characterised by size and crystal habit (monoclinic or triclinic). Structural analysis was carried out by x ray powder diffraction (XRD) and the proportions of monoclinic to triclinic CPPD were estimated from densitometric measurements of selected key reflections. RESULTS--The mean crystal size, by HRTEM, indicated that the crystals in the acute sample were larger than those in the interval sample. The ratio of monoclinic to triclinic CPPD, whether estimated from their morphological appearance by HRTEM, or from XRD, was greater in the acute than in the interval sample in all nine patients. The total amount of extracted mineral varied, but in every patient the concentration of CPPD per ml of fluid, and the total mineral per joint, were greater in the acute sample than in the interval sample. CONCLUSION--In this highly selected group of patients, the large numbers of CPPD crystals associated with attacks of pseudogout included a greater proportion of monoclinic crystals, and larger crystals, than those present when inflammation had subsided. A special, phlogistic population of crystals may exist, originating in different joint tissues, or cleared in a different manner, than the more common populations of smaller crystals with a greater proportion of triclinic CPPD, seen in chronic disease.